2019
DOI: 10.1002/jlb.ma0818-308r
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophils activated via TLR8 promote Th17 polarization through IL-23

Abstract: Human neutrophils contribute to the regulation of inflammation via the generation of a range of cytokines that affect all elements of the immune system. Here, we investigated their ability to express some of the members of the IL‐12 family after incubation with TLR8 agonists. Highly pure human neutrophils were thus incubated for up to 48 h with or without R848, or other TLR8 agonists, to then measure the expression levels of transcripts and proteins for IL‐12 family member subunits by RNA‐seq, reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 56 publications
5
36
0
Order By: Relevance
“…Of note, these results were validated by qPCR of selected key genes. Recently, Tamassia et al reported that the use of Adalimumab decreased the production of IL-23 protein as well as decreased levels of IL12B and IL23A transcripts in TLR-8 activated neutrophils (47). Indeed, the gene-expression profiling predicts a net effect of potent anti-inflammatory action by Adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these results were validated by qPCR of selected key genes. Recently, Tamassia et al reported that the use of Adalimumab decreased the production of IL-23 protein as well as decreased levels of IL12B and IL23A transcripts in TLR-8 activated neutrophils (47). Indeed, the gene-expression profiling predicts a net effect of potent anti-inflammatory action by Adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models of enthesitis also shown neutrophil infiltration . A recent human in vitro study showed that neutrophils showed greatest IL‐23 production when stimulated with TLR7/8 agonists as opposed to TLR4 . The physiological importance of neutrophil‐derived IL‐23, however, must be treated with caution.…”
Section: The Concept Of Il‐23–independent Il‐17 Productionmentioning
confidence: 99%
“…140 A recent human in vitro study showed that neutrophils showed greatest IL-23 production when stimulated with TLR7/8 agonists as opposed to TLR4. 141 The physiological importance of neutrophil-derived IL-23, however, must be treated with caution. A psoriasis mouse model that utilizes imiquimod (TLR7/8) agonist is dependent on IL-23 production in monocytes and not neutrophils.…”
Section: Myeloid Cells As Producers Of Il-23 In Manmentioning
confidence: 99%
“…Neutrophils also produce the Th17 differentiation cytokine IL-23 [36], their elastase release processes DC-derived CXCL8 into a Th17-promoting form [37], and in vitro they can induce Th17 differentiation directly [38]. However, the mechanisms through which this occurs largely remain unknown.…”
Section: Introductionmentioning
confidence: 99%